Pacientų įtraukties instrumentai sveikatos priežiūros paslaugų kokybei gerinti: Monografija - Jankauskienė, Danguolė; Mockevičienė, Birutė; Servetkienė, Vaida; Jankauskienė, Augustina; Ažukaitis, Karolis; Trinkūnas, Justas; Puronaitė, Roma; Vaitkevičienė, Goda Elizabeta; Černovas, Andrejus (2023)
PATIENT ENGAGEMENT INSTRUMENTS FOR IMPROVING THE QUALITY OF HEALTHCARE SERVICESThe success of health policy and the healthcare sector is increasingly measured in terms of the dynamics and changes in public trust in the healthcare system, the quality of services provided by healthcare facilities matching people’s expectations, and the fulfilment of patient needs. In order to ensure the required efficiency of public services and to provide better-quality and more accessible healthcare services that match the expectations of the population, it is necessary that the recipients of these services (patients) themselves are actively engaged in improvement processes. Therefore, increasing importance and value is placed on the engagement of the patient in the process of improving healthcare services as an active and informed participant of the healthcare system.
Keywords: health policy; healthcare services; patients